Innovative Traditional Pastry - Baking healthier choices - Amorim, Cláudia (2021)
[Excerpt] Introducing low-calorie prebiotic ingredients in pastry traditional products, to create healthier and functional pastry options for final consumers who either are driven by a healthy lifestyle or have a medical condition.